A highly selective and sensitive red-emitting fluorescent probe for visualization of endogenous peroxynitrite in living cells and zebrafish. Issue 10 (25th April 2019) - Li, Zilu; Liu, Caiyun; Yu, Chen; Chen, Yanan; Jia, Pan; Zhu, Hanchuang; Zhang, Xue; Yu, Yamin; Zhu, Baocun; Sheng, Wenlong
Abstract : A highly selective and sensitive red-emitting fluorescent probe was constructed to visualize endogenous peroxynitrite in living cells and zebrafish. Abstract : Peroxynitrite (ONOO − ) has been proven to participate in various physiological and pathological processes, and may also be a contributing factor in many diseases. In view of this, there is a need to develop detection tools for unambiguously tracking a small amount of endogenous ONOO − to reveal its exact mechanisms. In this paper, a colorimetric and red-emitting fluorescent probeRed-PN, based on a rhodamine-type fluorophore and hydrazide reactive site is described. The probeRed-PN possesses the advantages of rapid response (within 5 s), visual color change (from colorless to pink), preeminent sensitivity (detection limit = 4.3 nM) and selectivity. Because of these outstanding performances, it was possible to accurately detect endogenous ONOO − . It was encouraging that the probeRed-PN could be used effectively for tracking the relatively low levels of endogenous and exogenous ONOO − in living cells and zebrafish. Thus, it is envisioned that the probeRed-PN would have promising prospects in applications for imaging ONOO − in a variety of biological settings.